Analisis Pengaruh Bauran Pemasaran Terhadap Keputusan Konsumen Membeli Sepeda Motor Secara Kreditpada PT.Smart Multi Finance Pontianak - Muhammad Firman (Universitas Muhammadiyah Pontianak, 2014)
The purpose of this study was to determine the effect of the marketing mix for the consumer's decision to buy a motorcycle on credit at PT. Smart Multi Finance Pontianak. Form of research is descriptive method. Population in this study are all consumers who take credit motorcycle PT. Smart Multi Finance Pontianak. Samples selected 100 people who have used credit since 2012, which uses proportionated sample stratified random sampling. Data were collected through observation, interviews, questioneir. The data analysis technique used is a simple regression analysis. The analysis showed that the influence of both the manner and simultaneously t test or F-test that showed a significant effect of the marketing mix for the consumer's decision to buy a motorcycle on credit at PT. Smart Multi Finance Pontianak which proved that tcount> t table (18.933> 2.000) or the significance value of 0.000 <0.05 while the value of F ie 358.465> 2.11 (F table) or a significant F value is 0.000, which is smaller than 0.05. The coefficient of determination (R2) was 78.50%, and the remaining 21.50% is influenced by other variables outside of this research. Multiple correlation coefficient value (R) is 0.886, while 0.886 is while 0.886 lies in the 0,800 and 1,000 who had a very strong correlation.